The protective effect of Barringtonia racemosa ethanolic leaves extract on Eimeria papillata- induced mice / Nurul ‘Ain Nabilah Azmal - Azmal, Nurul ‘Ain Nabilah (2016)
Eimeria papillata is known to be one of the parasites of coccidiosis. It is a specific coccidian mat infect mice. Coccidiosis could cause huge economic loss to farmers due to the development of resistance by the parasites towards anti-coccidial drugs. Thus, the study was designed to evaluate anti-coccidiosus activity of Barringtonia racemosa, which is also known for its anti- tumour and anti-inflammatory effects. The study was aimed to determine the ability of B. racemosa in reducing the parasite burden; to observe the histophatological structure on the mucosal section, as well to examine the presence of Bcl-2 protein as the results of E. papillata induction in the mice. Mice were divided into 5 groups (A, B, C, D and E). Mice from Group A was the normal control (non-infected + saline) and mice from Group B were no infected but treated with 500 mg/kg b.wt. B. racemosa leaves extract. Groups C, D and E were induced with 1X103 oocysts/mL of E. papillata oocysts (day 0). Group C was the negative control group (infected but no treatment given), Group D was infected with E. papillata and given treatment of 500mg/kg b.wt of B. racemosa leaves extract while Group E (positive control) were infected mice and treated with 20 mg/kg b.wt of Toltrazuril. B. racemosa leaves extract were given orally for four consecutive days (day 1-4 post-infection) while Toltrazuril was given once (day 1 post-infection). Fecal samples were collected and oocysts count were determined on day 5 post-infection. The weight of mice were recorded on day 5 post-infection for analysis of weight change due to infection and treatment. Immediately after the oocysts count and weight measurement, mice were humanly sacrificed and jejuna samples were collected and prepared for histopathological and immunohistochanical analysis to examine the presence of Bcl-2 protein. The outcomes of this study showed that infected mice treated with B. racemosa leaves extract had significantly lower oocysts count compared to non-treated group. B. rucemosa extract also was able to prevent the reduction of weight in the infected group. The extract was also able to decrease the destruction on the overall mucosal structure (epithelial layer, villi length and crypt length) of jejunum in infected mice. Lower expression of Bcl-2 protein in infected mice treated with B. racemosa leaves extract indicated high apoptosis, hence, less prevention role of the extract against cell death induced by E. papillata. In conclusion, B. racemosa showed anti-coccidiosis activity at dose of 500 mg/kg b.wt by reducing the oocysts count but the low expression of Bcl-2 protein revealed that B. racemosa is less effective in protecting the jejunum against E. papillata infection. Therefore, it is suggested to conduct further research to determine the optimum dose of B. racemosu leaves extract that could possess protective effect against E. papillata infection on the JeJunum.